2015
DOI: 10.1097/bsd.0b013e31828ffc97
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Starting Point and Bicortical Purchase of C1 Lateral Mass Screws on Atlantoaxial Fusion

Abstract: The Goel-Harms technique is a very safe and successful technique for achieving atlantoaxial fusion, regardless of minor variations in C1LMS technique. Although biomechanical studies suggest markedly increased rigidity of bicortical and posterior arch C1LMS, the significance of these findings may be minimal in the clinical setting of atlantoaxial fixation and fusion with modern techniques. The decision to use either technique must be made after careful review of the preoperative multiplanar computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Our prospective, self-controlled comparative study demonstrated the advantages of the C1 pedicle screw technique, as superior to the C1 lateral mass screw technique; including less blood loss, shorter operative times, and fewer postoperative complications [53]. Thus, the C1 pedicle screw technique has become the most popular C1 screw technique [48,52,[54][55][56]. Many strategies of C1 pedicle screw placement have been introduced [36][37][38]57,58].…”
Section: C1 Screw Techniques C1 Lateral Mass Screw Techniquementioning
confidence: 95%
“…Our prospective, self-controlled comparative study demonstrated the advantages of the C1 pedicle screw technique, as superior to the C1 lateral mass screw technique; including less blood loss, shorter operative times, and fewer postoperative complications [53]. Thus, the C1 pedicle screw technique has become the most popular C1 screw technique [48,52,[54][55][56]. Many strategies of C1 pedicle screw placement have been introduced [36][37][38]57,58].…”
Section: C1 Screw Techniques C1 Lateral Mass Screw Techniquementioning
confidence: 95%
“…Before introduction of this method, the C1 LMS in our clinic was often just unicortical because the surgeon attempted to avoid excess anterior perforation. The unicortical screw exhibits strength 23) however, many studies recommended bicortical screwing.…”
Section: Discussionmentioning
confidence: 99%
“…Der Schutz der A. vertebralis ist, wie von den Kollegen beschrieben, essenziell, allerdings birgt diese modifizierte Technik unserer Meinung nach trotzdem eine höhere Gefahr der A.-vertebralis-Verletzung. Des Weiteren scheint die biomechanische Überlegenheit der C1-Pedikelschraube über die C1-Massa-lateralis-Schraube für die klinische Versorgung wenig relevant zu sein [1].…”
unclassified